2018
DOI: 10.1017/aer.2018.57
|View full text |Cite
|
Sign up to set email alerts
|

A general numerical unsteady non-linear lifting line model for engineering aerodynamics studies

Abstract: The lifting-line theory is widely used for obtaining aerodynamic performance results in various engineering fields, from aircraft conceptual design to wind-power generation. Many different models were proposed, each tailored for a specific purpose, thus having a rather narrow applicability range. This paper presents a general lifting-line model capable of accurately analysing a wide range of engineering problems involving lifting surfaces, both steady-state and unsteady cases. It can be used for lifting surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Further work [48,49] extended the frequency range before Guermond and Sellier [50] produced a method suitable for swept wings at any oscillation frequency. Research in the time domain has been less extensive, and asymptotically limited by the assumptions made in modeling the wake [51][52][53][54][55][56]. A more detailed review can be found in Bird and Ramesh [57].…”
mentioning
confidence: 99%
“…Further work [48,49] extended the frequency range before Guermond and Sellier [50] produced a method suitable for swept wings at any oscillation frequency. Research in the time domain has been less extensive, and asymptotically limited by the assumptions made in modeling the wake [51][52][53][54][55][56]. A more detailed review can be found in Bird and Ramesh [57].…”
mentioning
confidence: 99%
“…Bird et al [5] apply this method to a geometrically nonlinear inner solution. Sugar-Gabor et al [59] suggested a method where the unsteady wake was only accounted for in the outer 3D problem, allowing for roll and yaw kinematics. Lifting-line theory has also been used to model wings in large-scale simulations where resolving the chord-scale would be prohibitively expensive, for example, in Caprace et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] was extended to unsteady flows in ref. [40]. In the context of unsteady flows, the continuous distribution of bound vorticity over the lifting surface and of trailing vorticity in the wake are approximated using a finite number N of ring vortices bound to the geometry, and at each time step, a new row of N vortex rings are shed into the wake, as illustrated in Fig.…”
Section: Extensions To Unsteady Flowsmentioning
confidence: 99%
“…The various terms appearing in the above equation are lengthy and will not be presented here but can be found in full in ref. [40].…”
Section: Extensions To Unsteady Flowsmentioning
confidence: 99%